Renewable energy subsidies: Second-best policy or fatal aberration for mitigation? - Matthias Kalkuhl; Ottmar Edenhofer; Kai Lessmann (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper evaluates the consequences of renewable energy policies on welfare, resource rents and energy costs in a world where carbon pricing is imperfect and the regulator seeks to limit emissions to a (cumulative) target. We use a global general equilibrium model with an intertemporal fossil resource sector. We calculate the optimal second-best renewable energy subsidy and compare the resulting welfare level with an efficient first-best carbon pricing policy. If carbon pricing is permanently missing, mitigation costs increase by a multiple (compared to the optimal carbon pricing policy) for a wide range of parameters describing extraction costs, renewable energy costs, substitution possibilities and normative attitudes. Furthermore, we show that small deviations from the second-best subsidy can lead to strong increases in emissions and consumption losses. This confirms the rising concerns about the occurrence of unintended side effects of climate policy a new version of the green paradox. We extend our second-best analysis by considering two further types of policy instruments: (1) temporary subsidies that are displaced by carbon pricing in the long run and (2) revenue-neutral instruments like a carbon trust and a feed-in-tariff scheme. Although these instruments cause small welfare losses, they have the potential to ease distributional conflicts as they lead to lower energy prices and higher fossil resource rents than the optimal carbon pricing policy.
Keywords: Q4; Q52; Q54; Q58; D58; H21; 330; Feed-in-Tariff; Carbon Trust; Carbon Pricing; Supply-Side Dynamics; Green Paradox; Climate Policy